Preparation method and application of composite lithium ion sieve

By preparing composite lithium ion sieve, the problems of insufficient adsorption capacity and unstable structure during the lithium salt purification process of existing lithium ion sieve are solved, and efficient and economical lithium salt purification effect is achieved, and multiple recycling is supported.

CN119735238AInactive Publication Date: 2025-04-01ZHEJIANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411317563.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion sieves have insufficient adsorption capacity, unstable structure, easy to be deactivated and slow adsorption rate during the lithium salt purification process, resulting in high cost and poor performance.

Method used

By using the preparation method of composite lithium ion sieve, a composite lithium ion sieve with high selectivity and high adsorption capacity is prepared by ultrasonic stirring of lithium source, manganese carbonate, ammonium fluoride, aluminum chloride and deionized water, and calcining and acidification treatment at high temperature.

Benefits of technology

It achieves efficient purification of lithium salt, improves adsorption capacity, enhances selectivity, and has stable material structure, reduces costs, and supports multiple recycling, which is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite lithium ion sieve. The preparation method comprises the following specific steps: 1) adding a lithium source, manganese carbonate, ammonium fluoride and aluminum chloride into water, and ultrasonically stirring to uniformly mix; continuously drying and crushing the solid-liquid mixture; 2) transferring the solid into a muffle furnace for high-temperature calcination to obtain a black solid, namely a composite lithium ion sieve precursor; and 3) acidifying the composite lithium ion sieve, immersing the obtained precursor into diluted hydrochloric acid for a period of time, separating a solid-liquid mixture by using a centrifugal machine, and drying the precipitate to obtain the composite lithium ion sieve. Deionized water is used for cleaning residual ions on the surface of the solid, then absolute ethyl alcohol is used for cleaning residual deionized water on the surface, and finally the solid is dried to constant weight. The method is simple to operate, short in process flow, low in cost and good in product adsorption capacity cycle performance, overcomes the defects of high energy consumption and large occupied area of a traditional evaporation concentration method, and is beneficial to realizing industrialization of lithium salt purification with lower cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium salt purification, and provides a preparation method of a composite lithium ion sieve and its application, in particular, the preparation of a composite lithium ion sieve and its application in lithium salt purification. Background Art

[0002] With the increasing demand for lithium-ion batteries in power batteries, the overall price trend of related lithium salts such as lithium carbonate is constantly rising. Compared with traditional purification methods such as carbonization crystallization, lithium ion sieve adsorption has the advantages of high selectivity and low energy consumption. Therefore, it is of great significance to carry out research related to lithium ion sieve adsorption.

[0003] In lithium batteries, lithium salts are key components in the electrolyte, which largely determines the performance of the electrolyte, and thus affects the performance of the battery. Not only that, lithium carbonate or lithium hydroxide is also needed when synthesizing ternary positive electrode materials. When the purity of lithium salts is not high enough, it will seriously affect the purity of the electrolyte and positive electrode materials, causing a variety of side reactions during the reaction, which in turn affects the capacity and safety performance of the battery. Appropriate adsorption can purify lithium salts, which is crucial to the formation of electronic-grade lithium salts.

[0004] Spinel LiMn 2 O 4 It has a cubic crystal structure and belongs to the Fd3m space group. In this structure, Li + The tetrahedral 8a site is occupied, while Mn 3+ and Mn 4+ Arranged randomly at the position of octahedron 16d in a 1:1 ratio, O 2- Occupies the 32e position of the face-centered cubic. The lithium precursor forms a lithium ion sieve through Li-H ion exchange. As the lithium ions are stripped, empty lattice positions appear; based on the steric effect, the empty crystal position can only accommodate ions less than or equal to the radius of the lithium ion, selectively adsorbing Li + Its mechanism is simple and its operation process is short, making it a strong competitor for new and efficient methods of separating and purifying lithium salts in the future.

[0005] At present, there are many related lithium manganese oxides, and there are certain gaps in the synthesis and corresponding applications using various methods. The common adsorption capacity is generally 10-40 mg / g, which is not large enough, and common adsorbents also have the characteristics of unstable structure, easy deactivation, and slow adsorption rate. In order to save costs and increase the number of material cycles, it is necessary to improve the material and optimize its mode of action to improve its performance. Therefore, it is imperative to design a high-capacity and long-cycle lithium ion sieve. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method of a composite lithium ion sieve and its application to solve the problems existing in the existing methods. At the same time, the composite lithium ion sieve is used for adsorption-elution to efficiently purify lithium salts.

[0007] The present invention is synthesized by the following scheme:

[0008] A method for preparing a composite lithium ion sieve, the specific steps are as follows:

[0009] 1) The lithium source, manganese carbonate, ammonium fluoride, aluminum chloride and deionized water are stirred and ultrasonically mixed to be fully mixed, the solid-liquid mixture is dried, and after drying, the solid is crushed to a particle size of less than 50 microns to obtain a solid powder.

[0010] 2) The solid is then transferred to a muffle furnace for high-temperature calcination, and the resulting black solid is the composite lithium ion sieve precursor.

[0011] 3) The composite lithium ion sieve is acidified, and the specific operation is to immerse the precursor obtained in step 2) in dilute hydrochloric acid for a period of time, separate the solid-liquid mixture using a centrifuge, and dry the precipitate to obtain a composite lithium ion sieve. Use deionized water to wash the residual ions on the solid surface, then use anhydrous ethanol to wash the residual deionized water on the surface, and finally dry the solid to constant weight.

[0012] Preferably, the lithium source in step 1) should be at least one of lithium hydroxide, lithium carbonate and lithium oxalate.

[0013] Preferably, in step 1), lithium:manganese:aluminum:fluorine=1.03-1.08:2:0.05-0.2:0.05-0.2.

[0014] Preferably, in step 1), the stirring rate is 500-2000 rpm, the total stirring time is ≥30 min, and the total ultrasonic time is ≥30 min.

[0015] Preferably, in step 1), the ratio of the solid-liquid mixture is 1:1.0-1.5.

[0016] Preferably, the drying temperature in step 1) is 120-150° C. and the drying time is ≥ 24 h.

[0017] Preferably, in step 2), the high temperature calcination temperature is 700-750° C. and the time is 3-5 h.

[0018] Furthermore, the heating rate of high temperature calcination is 3-10°C / min.

[0019] Preferably, the temperature required for drying in step 2) is 120-150°C.

[0020] Preferably, the concentration of the dilute hydrochloric acid in step 3) is 0.01-0.1 mol / L.

[0021] Preferably, the dilute hydrochloric acid immersion time in step 3) is 30-60 minutes.

[0022] Preferably, in step 3), the number of water washings is 2-4 times, and the number of alcohol washings is 2-3 times.

[0023] Preferably, the drying temperature in step 3) is 60-80°C.

[0024] Preferably, the drying time in step 3) is 6-8 hours.

[0025] Compared with the existing patented technology, the technical advantages of the present invention are:

[0026] Compared with traditional evaporation concentration or extraction methods with organic pollution, the composite lithium ion sieve prepared by the present invention has high selectivity and high adsorption capacity, which can effectively shorten the lithium salt purification cycle and avoid the large-scale establishment of evaporation concentration pools, effectively reducing the cost of lithium salt purification. In addition, the process flow of the present invention is short, so the equipment and site costs are low; at the same time, the high-temperature calcination method can also be applied to large-scale production, which brings further cost advantages. Furthermore, after the lithium ion sieve is prepared, it can be recycled multiple times by the adsorption-elution method. This product has low environmental pollution, is safe and non-toxic, and has obvious social and economic benefits. DETAILED DESCRIPTION

[0027] The following technical solutions in the embodiments clearly and completely illustrate the specific content of the present invention, but the embodiments of the present invention are not limited thereto and should not be construed as limiting the scope of protection of the present invention. Any improvements and adjustments made by relevant experimenters in this field based on this patent without creative work shall fall within the scope of protection of the present invention.

[0028] In the following examples, unless otherwise specified, "%" used to indicate concentration refers to mass ratio, ":" used to indicate solid ratio refers to mass ratio, and ":" used to indicate liquid volume refers to volume ratio. Experimental methods without specifying specific experimental conditions were carried out according to common methods in research or operating methods recommended by manufacturers.

[0029] Example 1 A method for preparing a composite lithium ion sieve, the details are as follows:

[0030] Lithium hydroxide monohydrate, aluminum chloride and ammonium fluoride were added to deionized water and stirred for 15 minutes, and then manganese carbonate was added while stirring and continued to stir for 30 minutes at a stirring rate of 500 rpm. The mixture was then ultrasonicated for 30 minutes, and finally the solid-liquid mixture was stirred for 15 minutes. The molar ratio of lithium: manganese: aluminum: fluorine was 1.03:2:0.05:0.05, and the solid: water was 1:1. The obtained solid-liquid mixture was transferred to an oven, the oven temperature was set to 120°C, and the drying time was 48 hours. The dried solid was then crushed to less than 50 microns using a jet mill.

[0031] The above powder was placed in a muffle furnace for calcination at a temperature of 700°C for 3 hours at a heating rate of 3°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a composite lithium ion sieve precursor for later use.

[0032] The composite lithium ion sieve precursor was added to 0.05 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10 by mass, and soaked for 30 minutes. The suspension was taken out and separated by centrifuge. After the precipitate was taken out, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 3 times and then washed with ethanol 2 times. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 60°C and a drying time of 6 hours to obtain a composite lithium ion sieve with a relatively uniform particle size.

[0033] Example 2 A method for preparing a composite lithium ion sieve, the details are as follows:

[0034] Add lithium carbonate to deionized water and stir for 15 minutes, then add manganese carbonate while stirring and continue stirring for 30 minutes and ultrasonic for 30 minutes, then add aluminum chloride and ammonium fluoride to the mixture, and finally ultrasonicate the solid-liquid mixture for 15 minutes and stir for 15 minutes, with a stirring rate of 1000rpm. Among them, lithium: manganese: aluminum: fluorine = 1.05: 2: 0.1: 0.1, solid: water = 1: 1.2. The obtained solid-liquid mixture is transferred to an oven, the oven temperature is set to 150°C, and the drying time is 48 hours. Then use a jet mill to crush the dried solid to less than 50 microns.

[0035] The above powder was placed in a muffle furnace for calcination at a temperature of 750°C, a calcination time of 5 hours, and a heating rate of 5°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a composite lithium ion sieve precursor for later use.

[0036] The composite lithium ion sieve precursor was added to 0.01 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10 by mass, and soaked for 45 minutes. The suspension was taken out and separated by centrifuge. After taking out the precipitate, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 4 times and then washed with ethanol 3 times. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 80°C and a drying time of 8 hours to obtain a composite lithium ion sieve with a relatively uniform particle size.

[0037] Example 3 A method for preparing a composite lithium ion sieve, the details are as follows:

[0038] Add lithium hydroxide, aluminum chloride and ammonium fluoride to deionized water and stir for 30 minutes, then add manganese carbonate while stirring and continue stirring for 45 minutes, the stirring rate is 2000rpm, then ultrasonicate the mixture for 30 minutes, and finally stir the solid-liquid mixture for 30 minutes. Among them, lithium: manganese: aluminum: fluorine = 1.08: 2: 0.2: 0.2, solid: water = 1: 1.5. The obtained solid-liquid mixture is transferred to an oven, the oven temperature is set to 150℃, and the drying time is 24 hours. Then use a jet mill to crush the dried solid to less than 50 microns.

[0039] The above powder was placed in a muffle furnace for calcination at a temperature of 730°C, a calcination time of 5 hours, and a heating rate of 8°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a composite lithium ion sieve precursor for later use.

[0040] The composite lithium ion sieve precursor was added to 0.1 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10 by mass, and soaked for 30 minutes. The suspension was taken out and separated by centrifuge. After taking out the precipitate, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 4 times and then washed with ethanol twice. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 70°C and a drying time of 8 hours to obtain a composite lithium ion sieve with a relatively uniform particle size.

[0041] Comparative Example 1 A method for preparing a manganese oxide ion sieve, the details are as follows:

[0042] Add lithium hydroxide monohydrate to deionized water and stir for 15 minutes, then add manganese carbonate while stirring and continue stirring for 30 minutes, the stirring rate is 500rpm, then ultrasonicate the mixture for 30 minutes, and finally stir the solid-liquid mixture for 15 minutes. Among them, lithium: manganese = 1.03:2, solid: water = 1:1. The obtained solid-liquid mixture is transferred to an oven, the oven temperature is set to 120℃, and the drying time is 48 hours. Then use a jet mill to crush the dried solid to less than 50 microns.

[0043] The above powder was placed in a muffle furnace for calcination at a temperature of 700°C for 3 hours at a heating rate of 3°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a manganese oxide ion sieve precursor for later use.

[0044] The manganese oxide ion sieve precursor was added to 0.05 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10, and soaked for 30 minutes. The suspension was taken out and separated by a centrifuge. After the precipitate was taken out, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 3 times and then washed with ethanol 2 times. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 60°C and a drying time of 6 hours to obtain a manganese oxide ion sieve with a relatively uniform particle size.

[0045] Comparative Example 2 A method for preparing a manganese oxide ion sieve, the details are as follows:

[0046] Add lithium carbonate to deionized water and stir for 15 minutes, then add manganese carbonate while stirring and continue ultrasonication for 30 minutes and stirring for 30 minutes, with a stirring rate of 1000rpm. Among them, lithium: manganese = 1.05:2, solid: water = 1:1.2. The obtained solid-liquid mixture is transferred to an oven, the oven temperature is set to 150℃, and the drying time is 48 hours. Then use a jet mill to crush the dried solid to less than 50 microns.

[0047] The above powder was placed in a muffle furnace for calcination at a temperature of 750°C, a calcination time of 5 hours, and a heating rate of 5°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a manganese oxide ion sieve precursor for later use.

[0048] The manganese oxide ion sieve precursor was added to 0.01 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10, and soaked for 45 minutes. The suspension was taken out and separated by centrifuge. After the precipitate was taken out, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 4 times and then washed with ethanol 3 times. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 80°C and a drying time of 8 hours to obtain a manganese oxide ion sieve with a relatively uniform particle size.

[0049] Comparative Example 3 A method for preparing a manganese oxide ion sieve, the details are as follows:

[0050] Add lithium hydroxide to deionized water and stir for 30 minutes, then add manganese carbonate while stirring and continue stirring for 45 minutes, the stirring rate is 2000rpm, then ultrasonicate the mixture for 30 minutes, and finally stir the solid-liquid mixture for 30 minutes. Among them, lithium: manganese = 1.08:2, solid: water = 1:1.5. The obtained solid-liquid mixture is transferred to an oven, the oven temperature is set to 150℃, and the drying time is 24 hours. Then use a jet mill to crush the dried solid to less than 50 microns.

[0051] The above powder was placed in a muffle furnace for calcination at a temperature of 730°C, a calcination time of 5 hours, and a heating rate of 8°C / min. After the muffle furnace was cooled, the sample was taken out and ground into powder using a grinder to obtain a manganese oxide ion sieve precursor for later use.

[0052] The manganese oxide ion sieve precursor was added to 0.1 mol / L dilute hydrochloric acid at a solid-liquid ratio of 1:10, and soaked for 30 minutes. The suspension was taken out and separated by centrifuge. After the precipitate was taken out, deionized water was added at a ratio of 1:1 and centrifuged again. The water washing was repeated 4 times and then washed with ethanol twice. After the water washing was completed, the precipitate was transferred to an oven at a temperature of 70°C and a drying time of 8 hours to obtain a manganese oxide ion sieve with a relatively uniform particle size.

[0053] Comparative Example 4

[0054] This comparative example provides a preparation method of a composite lithium ion sieve, which is basically the same as that of Example 1, except that the concentration of hydrochloric acid used for soaking is 0.001 mol / L.

[0055] Comparative Example 5

[0056] This comparative example provides a preparation method of a composite lithium ion sieve, which is basically the same as that of Example 1, except that the concentration of hydrochloric acid used for soaking is 0.01 mol / L.

[0057] Comparative Example 6

[0058] This comparative example provides a method for preparing a composite lithium ion sieve, which is basically the same as that of Example 1, except that the concentration of hydrochloric acid used for soaking is 0.1 mol / L.

[0059] Comparative Example 7

[0060] This comparative example provides a preparation method of a composite lithium ion sieve, which is basically the same as that of Example 1, except that the concentration of hydrochloric acid used for soaking is 0.15 mol / L.

[0061] Comparative Example 8

[0062] This comparative example provides a preparation method of a composite lithium ion sieve, which is basically the same as that of Example 1, except that the concentration of hydrochloric acid used for soaking is 0.2 mol / L.

[0063] Test Example 1

[0064] Application of composite lithium ion sieve and manganese oxide lithium ion sieve in lithium salt purification

[0065] Adsorption capacity and selectivity experiment: First, take some salt lake water to determine its initial Li + 、Na + Mg 2+ , K + , Ca 2+ The composite lithium ion sieve and manganese oxide lithium ion sieve prepared in the embodiment and the comparative example were added into the salt lake water at 10 g / L, the mixed liquid was stirred at room temperature for 10 h, and the Li + 、Na + Mg 2+ , K + , Ca 2+ Concentration. Then use the formula Calculate the adsorption capacity.

[0066] Where Q E is the saturated adsorption capacity, C 0 is the initial concentration of lithium ions, C E is the concentration of lithium ions after adsorption,

[0067] Test Example 2

[0068] Manganese dissolution experiment: After the above adsorption experiment is completed, dilute hydrochloric acid is used to desorb the lithium ion sieve. During the desorption process, Li + -H + Ion exchange, at the same time, because manganese is easy to undergo disproportionation reaction in acid solution, a small amount of manganese will be removed from the lithium ion sieve. By measuring the mass of manganese in the solution after desorption, the formula R = Calculate the amount of manganese dissolved.

[0069] Where R is the dissolution rate, M y is the mass of manganese after desorption, M s is the mass of manganese in the lithium ion sieve.

[0070] The results are shown in Table 1

[0071] Table 1

[0072] Lithium adsorption capacity mg / g Li / Na Li / Mg Li / K Li / Ca Dissolution rate / % Example 1 32.62 25.64 100.52 90.54 78.85 0.72 Example 2 31.29 22.34 98.71 91.32 68.53 0.85 Example 3 30.87 21.98 97.62 89.47 62.54 0.79 Comparative Example 1 25.68 14.32 34.43 36.77 48.21 2.45 Comparative Example 2 28.72 15.00 36.87 38.73 42.14 2.56 Comparative Example 3 27.63 13.59 34.82 32.54 38.64 2.49 Comparative Example 4 20.68 24.33 98.22 89.33 76.35 0.68 Comparative Example 5 24.32 24.85 99.65 89.46 77.38 0.71 Comparative Example 6 33.28 25.03 100.49 89.69 78.76 0.78 Comparative Example 7 35.73 25.42 100.61 90.03 78.91 0.82 Comparative Example 8 36.25 25.37 100.28 90.28 78.71 1.03

[0073] As can be seen from Table 1, the adsorption capacity and selectivity of the embodiment are higher than those of the comparative example, while its dissolution rate is much lower than that of the comparative example. The reason is that the addition of aluminum element to lithium manganese oxide introduces aluminum-oxygen bonds, enhances the bond energy and makes the structure more stable and reliable, so its dissolution rate will be reduced; at the same time, the F element modifies the surface of the material, increases the contact area between the composite lithium ion sieve particles and the solution, enhances its lithium ion migration kinetics, and thus increases the adsorption capacity of lithium ions. At the same time, with the increase of the concentration of hydrochloric acid for immersion, the lithium adsorption capacity gradually increases, but the dissolution rate of manganese also increases accordingly.

[0074] In summary, the composite lithium ion sieve of the present invention has the characteristics of high adsorption capacity, good selectivity and low dissolution rate during the adsorption process.

Claims

1. A method for preparing a composite lithium ion sieve, characterized in that: Here are the steps: 1) adding lithium source, manganese carbonate, ammonium fluoride and aluminum chloride into water and stirring them ultrasonically to make them uniformly mixed; and continuing to dry and crush the solid-liquid mixture; 2) The crushed solid is transferred to a muffle furnace for high-temperature calcination, and the resulting black solid is a composite lithium ion sieve precursor; 3) The composite lithium ion sieve precursor is acidified, and the obtained precursor is immersed in dilute hydrochloric acid for a period of time, and then the solid-liquid mixture is separated by a centrifuge, and the precipitate is dried to obtain a composite lithium ion sieve. The residual ions on the solid surface are washed with deionized water, and then the residual deionized water on the surface is washed with anhydrous ethanol, and finally the solid is dried to constant weight.

2. The method for preparing a composite lithium ion sieve according to claim 1, characterized in that: In step 1), the lithium source should be at least one of lithium hydroxide, lithium carbonate and lithium oxalate.

3. The method for preparing a composite lithium ion sieve according to claim 1, characterized in that: In step 1), the molar ratio of lithium: manganese: aluminum: fluorine element is 1.03-1.08: 2: 0.05-0.2: 0.05-0.

2.

4. A method for preparing a composite lithium ion sieve according to claim 1 or 3, characterized in that: In step 1), the stirring rate is 500-2000 rpm, the total stirring time is ≥30 min, and the total ultrasonic time is ≥30 min.

5. The method for preparing a composite lithium ion sieve according to claim 1 or 3, characterized in that: In step 1), the solid-liquid mass ratio in the solid-liquid mixture is 1:1.0-1.

5.

6. The method for preparing a composite lithium ion sieve according to claim 1, characterized in that: In step 1), the drying temperature is 120-150°C and the drying time is ≥ 24h.

7. The method for preparing a composite lithium ion sieve according to claim 1, characterized in that: In step 2), the high temperature calcination temperature is 700-750°C, the time is 3-5h, and the heating rate of the high temperature calcination is 3-10°C / min.

8. The method for preparing a composite lithium ion sieve according to claim 5, characterized in that: In step 3), the concentration of dilute hydrochloric acid is 0.01-0.1 mol / L.

9. The method for preparing a composite lithium ion sieve according to claim 8, characterized in that: In step 3), the dilute hydrochloric acid immersion time is 30-60 minutes.

10. The method for preparing a composite lithium ion sieve according to claim 1, characterized in that: In step 3), the water washing times are 2-4 times, the alcohol washing times are 2-3 times, the drying temperature is 60-80° C., and the drying time is 6-8 hours.

Citation Information

Patent Citations

  • Preparation method of lithium ion sieve adsorbent and method for adsorbing lithium ions

    CN107138126A

  • Preparation method of lithium ion sieve

    CN110898794A